Pengujian Aktivitas Antibakteri dari Fraksi N-heksan dan Etil asetat Tumbuhan Keji Besi (Hemigraphis Repanda) (L) terhadap Bacillus cereus - Katamang, Eden Eljire Imanuel; Walean, Mario; Tumiwa, Novita Natalia Gabriela; Manawan, Fridly (Prosiding Seminar Nasional Kefarmasian Program Studi Farmasi FMIPA Universitas Sam Ratulangi, 2024)
Bacillus cereus is one of the bacteria that causes diarrhea. Keji besi is a plant that is ethnomedically used by the community to treat several types of diseases such as fever, fungal infections of the baby's tongue and one of them is diarrhea. However, there has been no scientific study investigating the antibacterial activity of keji besi against B. cereus. This study aims to determine the antibacterial activity of the N-hexane fraction and ethyl acetate fraction of keji besi against B. cereus and also identify the fraction that exhibits the strongest antibacterial activity. The research employed a laboratory experimental design using a completely randomized design (CRD) with seven treatments, including a positive control (ciprofloxacin), negative control (DMSO), and five concentration variations for antibacterial testing (4 mg/20 μL, 8 mg/40 μL, 10 mg/50 μL, 12 mg/60 μL, and 14 mg/70 μL), repeated three times. The well-diffusion method was used for antibacterial testing, involving the creation of multiple holes in solid agar media inoculated with the test bacteria and subsequently filling the holes with the samples to be tested. The results showed that the N-hexane and ethyl acetate fractions of keji besi had antibacterial activity against B. cereus. Among them, the ethyl acetate fraction exhibited the greatest antibacterial activity with an inhibition zone diameter of 5.4 ± 1.2 mm at a concentration of 14 mg/70 μL, categorized as weak inhibition. Keywords: Keji Besi (Hemigraphis repanda) (L), Antibacterial activity, N-hexane, Ethyl acetate, Fraction, Bacillus cereus. Abstrak